Scientific evidence for the control of antimicrobial resistance (2020)
[Extract]. Antimicrobial resistance (AMR) is one of the greatest global threats to human health. It is estimated that by 2050, AMR will lead to approximately 10 million annual deaths worldwide. Considering the impact of AMR on reproductive capacity and food production, in addition to its direct effect on infected people, the world's population could drop by between 11 and 444 million inhabitants by 2050 if AMR control is not achieved. As migrations and shared economies lead to the transmission of resistant bacteria across borders, the impacts of AMR become regionally significant. In the United States, methicillin-resistant Staphylococcus aureus caused 10 600 deaths in 2017. In Latin American and Caribbean countries, information is available from studies conducted in hospitals and other health facilities on the prevalence of antimicrobial-resistant pathogens. In many hospitals in Mexico, Peru, and Colombia, for example, resistance to third-generation cephalosporins and fluoroquinolones in Escherichia coli isolates is reaching almost 60%. Moreover, the dynamics of colonization and infection of multidrug-resistant organisms (such as carbapenemaseproducing Klebsiella pneumoniae) are unique in endemic areas of Latin America, favoring spread and dissemination. [...]